MEMAKNAI NILAI-NILAI PEDOMAN HIDUP ISLAMI WARGA MUHAMMADIYAH PADA PROSES PENGANGGARAN STIE MUHAMMADIYAH PALOPO - Indah Pratiwi; Sukri Sukri (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2022)
It is very necessary to enlighten all elements of Muhammadiyah's business charity management to make and apply the values ​​of the life guidelines of Muhammadiyah citizens in every policy and activity in the association without exception. The purpose of this study is to interpret the values ​​of Islamic life guidelines for Muhammadiyah residents in the STIE Muhammadiyah Palopo budgeting system. The researcher will use the Islamic life guidelines for Muhammadiyah residents as a researcher's perspective in observing the activities of the budgeting system at STIE Muhammadiyah Palopo whether the values ​​of these guidelines are used as one of the considerations in the operation of the budgeting system at STIE Muhammadiyah Palopo in accordance with the expectations of Muhammadiyah's vision. This study found that the budget as a form of welfare is not only valued in nominal terms in the form of rupiah earned, but welfare is when people who work at Muhammadiyah always feel sufficient and grateful for the sustenance that Allah SWT has given. As a Muhammadiyah citizen, working in a Muhammadiyah business charity is a comfort in itself and believes that the sincerity they do will be a welfare for them in the hereafter. With their sincerity in working in the charity business of Muhammadiyah, they get rewards from Allah SWT such as unexpected sustenance and blessings in the income they get. STIE Muhammadiyah Palopo provides convenience, relief, and assistance in paying tuition fees for students. STIE Muhammadiyah Palopo provides facilities and assistance to students as a form of social care and appreciation for cadres, namely the Lazismu Scholarship, Incidental Assistance, Relief for Brothers, and the free SPP Alumni of SMA/SMK Muhammadiyah Palopo